Die Todesurteile des Kammergerichts 1943 bis 1945 : eine Dokumentation - Tuchel, Johannes 1957- HerausgeberIn; Lukas Verlag für Kunst- und Geistesgeschichte; Gedenkstätte Deutscher Widerstand; Forum Recht und Kultur im Kammergericht (Lukas Verlag, 2016)
Although the Berlin Kammergericht brought many verdicts against political opponents and critics of the regime after 1934, its role as part of the Nazi persecution apparatus has been little studied. Between 1943 and 1945, the Kammergericht handed at least 69 death sentences to resistance fighters and forced workers. This book brings together previously inaccessible biographical information about these victims of the legal actions of the Kammergericht. For the first time, six indictments and 19 sentences of death have been documented and analyzed